ALLEVIATING ACUTE PAIN TO RESTORE FUNCTION: A NURSING-LED GINGER OIL INTERVENTION FOR A FARMER WITH RHEUMATOID ARTHRITIS - Fitriah Effendy; Bagus Dwi Cahyono; Evy Aristawati; Nurul Huda; Apriana Rahmawati; Ronal Surya Aditya (Spectra Clinical Case Reports Journal, 2025)
Rheumatoid arthritis is a chronic autoimmune disease causing persistent joint inflammation, pain, stiffness, and progressive functional decline, particularly exacerbated among farmers by repetitive non-ergonomic labor. This case involved a 74-year-old male farmer from Pasuruan Regency, Indonesia, who presented with severe functional limitations. Assessment revealed throbbing joint pain rated 7 out of 10 on the Numeric Rating Scale, prolonged morning stiffness, fatigue with minimal exertion, slow and assisted gait, and dependence on family for ambulation and self-care. The priority of nursing diagnosis was Acute Pain related to inflammatory joint process and mechanical stress, per the Standar Diagnosis Keperawatan Indonesia, as uncontrolled pain was the primary barrier to physical function; activity intolerance was identified as a secondary diagnosis. The purpose of this case report was to evaluate the effectiveness of a nursing-led, non-pharmacological intervention topical ginger (Zingiber officinale) extract oil combined with massage in reducing acute pain and thereby improving functional capacity in a rural rheumatoid arthritis patient with limited access to pharmacotherapy. The intervention plan consisted of twice-daily application of ginger oil to knees and ankles with 10-minute gentle massage over three consecutive days, integrated with health education on activity pacing and light stretching. Following the intervention, pain intensity decreased to 3/10, ambulation improved from assisted to independent, and the patient resumed light farming and self-care tasks without frequent rest. No adverse effects occurred. These outcomes suggest that targeted pain management using locally available ginger oil may rapidly enhance activity tolerance in resource-limited settings. Further research is warranted to confirm efficacy and safety in larger cohorts.